Exclosure land management restores soil properties of degraded communal grazing lands in northern Ethiopia - Mekuria, Wolde; Aynekulu, Ermias (Wiley, 2013)
In the northern highlands of Ethiopia, establishment of exclosures to restore degraded communal grazing lands has been practiced for the past three decades. However, empirical data on the effectiveness of exclosures in restoring degraded soils are lacking. We investigated the influence of exclosure age on degree of restoration of degraded soil and identified easily measurable biophysical and management-related factors that can be used to predict soil nutrient restoration. We selected replicated (n = 3) 5-, 10-, 15-, and 20-year-old exclosures and paired each exclosure with samples from adjacent communal grazing lands. All exclosures showed higher total soil nitrogen (N), available phosphorus (P), and cation exchange capacity than the communal grazing lands. The differences varied between 2!4 ("0!61) and 6!9 ("1!85) Mgha#1 for the total N stock and from 17 ("3) to 39 ("7) kg ha#1 for the available P stock. The differences in N and P increased with exclosure age. In exclosures, much of the variability in soil N (R2=0!64) and P (R2=0!71) stocks were explained by a combination of annual average precipitation, woody biomass, and exclosure age. Precipitation and vegetation canopy cover also explained much of the variability in soil N (R2=0!74) and P (R2=0!52) stocks in communal grazing lands. Converting degraded communal grazing lands into exclosures is a viable option to restore degraded soils. Our results also con"rm that the possibility to predict the changes in soil nutrient content after exclosure establishment using regression models is based on "eld measurements.